First record of North American ambrosia beetle Gnathotrichus materiarius (Fitch) (Coleoptera, Scolytidae) in Finland - a new potential forest pest? - Valkama, Heli; Martikainen, Petri; Räty, Mika (Entomologica Fennica, 1997)
The North American ambrosia beetle Gnathotrichus materiarius is reported for the first time in Finland. One specimen was caught by a Ips typographus pheromone trap in Vantaa in 1996. The species was introduced to Europe from North Americain 1933, and since then it has spread to many Middle European countries. It is possible that this species has already become established in Fennoscandia, because of repeated introductions.